SUSTAINABLE STRATEGIES IN CONSTRUCTION SITES: EVALUATION OF ECO-EFFICIENT METHODOLOGIES FOR ENVIRONMENTAL IMPACT REDUCTION - Araújo Silva Duarte, Nianylla (Journal of Interdisciplinary Debates, 2025)
The civil construction industry is recognized as one of the largest consumers of natural resources and generators of waste, exerting a significant environmental impact. This article presents a systematic literature review (SLR) with the objective of evaluating the eco-efficient methodologies applied in construction sites and quantifying their effectiveness in reducing environmental impact. The PICO methodology (Population, Intervention, Comparison, Outcomes) was employed to guide the search in high-impact databases. The results revealed four main categories of strategies: Construction and Demolition Waste Management (CDW), Energy and Water Efficiency, Logistics and Process Optimization (Lean Construction), and Material Selection. The most relevant performance metrics include the Waste Diversion Rate (WDR), Water Consumption per Built Area (WCA), and Carbon Intensity. The critical analysis demonstrated that the integrated implementation of these methodologies can achieve reductions of 70% to 95% in CDW diversion to landfills and 30% to 50% in potable water consumption. It is concluded that the adoption of eco-efficient methodologies is crucial for sector sustainability, but the standardization of performance metrics is a research gap that needs to be addressed.